Potentially inappropriate medication use among older patients attending a geriatric centre in south-west Nigeria - Akande-Sholabi W; Adebusoye LA, Olowookere OO; Olowookere OO (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objectives: To determine the prevalence and describe factors associated with the use of potentially inappropriate medication (PIM) among older patients. Methods: Cross sectional study of 400 older patients selected systematically at the geriatric centre, University College Hospital, Ibadan between July and September 2016. With the aid of semi-structured questionnaires, information on the socio-demographic characteristics, lifestyle habits, healthcare utilisation and morbidities was obtained. The Beer's criteria 2015 update was used to identify the PIMs. Predictors of PIMs were determined using multivariate analyses at alpha 0.05. Results: Age was 70.2 (SD=5.9) years and 240 (60%) were females. General prescription pattern showed antihypertensives (34.7%) as the commonest medications used. The point prevalence of PIMs use was 31%. In all, 10 PIMs were used by the respondents. The majority (81.5%) were using one PIM, while (17.7%) used two PIMs and (0.8%) 3 PIMs. NSAIDs (72.6%) were the commonest PIMs identified, followed by the benzodiazepines (24.2%). Respondents had an average of 1.9 morbidities, and mulitmorbidity found in 60.5%. Logistic regression analysis showed self-rated health assessed as better compared with age-mates [OR =1.718 (1.080-2.725)] and being physically active [OR =1.879 (1.026-3.436)] as the most significantly associated with PIMs use. Conclusions: The use of PIMs among older patients in our setting was high with NSAIDs being the most frequently used medications. An interdisciplinary approach, of medication review by pharmacists', working with physicians may improve prescribing practices among older persons. Therefore, it is necessary to create public health awareness on the use of PIMs among older persons.